Analysis the Effect of Financial Statement Publication on the Stock Performance of PT Bank Syariah Indonesia Tbk. One Year after the Merger - wulansari wulansari; Diaz Perdana (UNUSA Press, 2022)
As the country with the world’s largest Muslim population, Indonesia has the potential to lead the Islamic finance industry. Increased public awareness of halal issues, as well as strong stakeholder support, are critical factors in the growth of Indonesia’s halal industry ecosystem. Islamic banks are included. BUMN Banks’ Sharia Banks, namely Bank Syariah Mandiri, BNI Syariah, and BRI Syariah, are no exception, having merged on February 1, 2021. The goal of this study was to see what effect the publication of quarterly financial statements had on the performance of PT Bank Syariah Indonesia’s stock price up to a year after the merger. This study employs secondary data and documentation techniques, with the analysis time period being each quarter in the annual period of 10 days after reporting financial publication reports and 10 days before reporting financial publication reports. Stock prices from that time period, as well as several financial ratios from publicly available financial reports, were used as variables. To test the hypothesis itself, use a ratio scale and the comparative hypothesis method of two paired sample t-tests, as well as the Ryan-Joiner method to test for normality. If the significance value is 0.05 or greater, the data is said to be normally distributed. According to the results of the tests, there were significant differences in BRIS stock prices 10 days before and 10 days after the financial statements were published.